The genus Paraplotes Laboissière, 1933 in Taiwan, a speciose group with brachelytrous females (Coleoptera: Chrysomelidae: Galerucinae) - Lee, Chi-Feng (Zootaxa, 2015)
Taiwanese members of the genus Paraplotes comprise a group of species that are not distinguishable based on external morphology but are diagnosed using distributions, aedeagal, and gonocoxal morphologies. Females of all species are brachelytrous. The group includes one previously described species, Paraplotes taiwana Chûjô, 1963, and nine new species, P. cheni sp. nov., P. jengi sp. nov., P. meihuai sp. nov., P. tahsiangi sp. nov., P. tatakaensis sp. nov., P. tsoui sp. nov., P. tsuenensis sp. nov., P. yaoi sp. nov., and P. yuae sp. nov. Diagnostic characters and hind wings of both sexes are illustrated. Models of speciation for the high diversity of Paraplotes in Taiwan are discussed. A novel hypothesis for brachelytrous leaf beetles occurring in tropical forest habitats (selva) is proposed.